DECISION MODEL FOR SUPPLIER EVALUATION AND SELECTION IN PROCESS INDUSTRY: A HYBRID DEA APPROACH - Pitchipoo, Pandian; Venkumar, Ponnusamy; Rajakarunakaran, Sivaprakasam; Ragavan, R (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The supplier selection and purchasing decision in any supply chain have become key decisions because it provides opportunities to reduce costs and, consequently, increase profits. The cost of purchase represents the largest percentage of the total product cost. Hence the supplier selection draws the interest of the researchers because selection of supplier is not only a cost reduction technique but also an important process to add the value to the products. Supplier selection is a complex problem which contains multiple criteria. In this paper, a decision model was developed based on data envelopment analysis (DEA) and the weights were calculated using Analytic hierarchy process (AHP), Entropy measurement technique and Revised Simos Procedure (RSP). Finally the results were compared with the help of a case study performed in a chemical processing industry. The novelty of this work is in the application of hybrid approaches to a chemical processing industry case.